1997
DOI: 10.1292/jvms.59.431
|View full text |Cite
|
Sign up to set email alerts
|

Structural Organization and Chromosomal Assignment of the Swine Endothelin-1 Gene.

Abstract: ABSTRACT. Cosmid clone containing swine endothelin-1 (EDN1) gene, cosEDN1, was isolated from swine cosmid library using swine EDN1 cDNA as a probe. The sequence analysis of cosEDN1 DNA revealed that the swine EDN1 gene consists of 5 exons, spanning approximately 6.5 kb. In the 5'-upstream region of the EDN1 gene, AP-1 and NF-1 elements were found, suggesting the possibility that the expression of swine EDN1 gene is controlled by protooncogene products Fos and Jun, and TGF-β. Fluorescence in situ hybridization … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

1998
1998
2019
2019

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 20 publications
(26 reference statements)
0
2
0
Order By: Relevance
“…c‐JUN is a component of AP‐1, a heterodimer consisting of c‐FOS and c‐JUN subunits. Notch has been reported to downregulate AP‐1 complex (Chu & Bresnick, ), and AP‐1 has been shown to regulate EDN1 transcription (Kawana, Lee, Quertermous, & Quertermous, ; Kojima, Ohata, & Yasue, ; Stricklett, Strait, & Kohan, ). Western blot analysis confirmed that NICD1 overexpression caused a marked downregulation in c‐JUN and phospho‐c‐JUN in MAPKi‐resistant MRA‐5 cells, whereas c‐JUN and phospho‐c‐JUN levels showed a slight increase in NICD1‐transduced MAPKi‐sensitive MRA‐6 cells (Figure d).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…c‐JUN is a component of AP‐1, a heterodimer consisting of c‐FOS and c‐JUN subunits. Notch has been reported to downregulate AP‐1 complex (Chu & Bresnick, ), and AP‐1 has been shown to regulate EDN1 transcription (Kawana, Lee, Quertermous, & Quertermous, ; Kojima, Ohata, & Yasue, ; Stricklett, Strait, & Kohan, ). Western blot analysis confirmed that NICD1 overexpression caused a marked downregulation in c‐JUN and phospho‐c‐JUN in MAPKi‐resistant MRA‐5 cells, whereas c‐JUN and phospho‐c‐JUN levels showed a slight increase in NICD1‐transduced MAPKi‐sensitive MRA‐6 cells (Figure d).…”
Section: Resultsmentioning
confidence: 99%
“…To understand the mechanism of action of NICD1 in regulation of EDN1, we identified a list of genes reported to mediate the effect of Notch signaling and also regulate EDN1 based on a curated PubMed search (Poon, Quirk, DeZiel, & Heckerman, 2014). We AP-1 complex (Chu & Bresnick, 2004), and AP-1 has been shown to regulate EDN1 transcription (Kawana, Lee, Quertermous, & Quertermous, 1995;Kojima, Ohata, & Yasue, 1997;Stricklett, Strait, & Kohan, 2011). Western blot analysis confirmed that NICD1 over-…”
Section: Role Of C-jun In the Mechanism Of Action Of Nicd1mentioning
confidence: 99%